CBPPRS: Cluster Based Privacy Preserving Routing Selection in Wireless Networks - Jayaprakash, R; Radha, B (International Journal of Engineering and Technology, 2018)
The In wireless mobile ad hoc network, each node / junction is proficient of transfer message (information) with dynamism without constraint of any permanent infrastructure environment. Movable nodes commonly progress inside or outside from the entire network dynamically, building network topology unbalanced in mobile ad-hoc network (MANET). In a privacy preserving network group, cluster head is dependable for communication with associates in a cluster which consumes additional battery (energy) supremacy in evaluation to cluster members in a cluster. As a message transmission inside and outside cluster as a result, it becomes an enormously testing job to maintain stability in network. In this paper aims to present a cluster based privacy preserving routing protocol selection algorithm in inside and outside cluster using NS (Network Simulator) 2.34 Framework. The proposed routing protocol selection based Cluster head selection formation operates exclusively based on source routing and on-demand process, it has been selected as the routing protocol to be executed and tested for ad hoc network application characterized by a source on-demand message conversation between nodes in a portable ad hoc networkÂ
Keywords: Cluster; Cluster Head; Gateway; Privacy Preserving; Wireless Networks.